Periradicular tissues reaction to the filling materials - A. Khayat (Tehran University of Medical Sciences, 1989)
Endodontic treatments are based on complete cleansing of root canal as well a multidimensional obturation especially in apical foramen area.  This study was done to analyze  the reactions of periradicular tissues to filling materials in case of  overobturation in endodontic treatments and healing despite extra filling material existence in periradicular tissues. 25 teeth with periradicular lesions (endodontic origin) in patients of 13-85 years were selected. 7 groups were formed based on the time of performing surgical biopsy on the teeth.  In 80% of the cases, despite existing extra materials in periradicular tissues, 100% bone healing as well as collagen formation was observed. Besides, some Giant cells and hemosiderine were found around the areas containing sealer.